APLIKASI FILTER PASIF SEBAGAI PEREDUKSI HARMONIK PADA INVERTER TIGA FASE - Wahri Sunanda; Yuli Asmi Rahman (Foristek, 2012)
Harmonic is one of sinusoidal components, one wave period from which having multiple frequency of its fundamental frequency one, leading to electrical power quality problems. Harmonic distortion in term of voltage and current ones, generally is due to non linier impedance. Inverter is one of example of it. There are some items that will be measured. There are value of harmonic at source and value of voltage and current harmonic when inverter does not have any load. IEEE Standard of 519-1992 as a reference in determining maximum limitation voltage and current harmonics. The result of the tests were showed that voltage harmonic distortion at inverter did not exceed the IEEE 519-1992 maximum limitation of 5%. While current harmonic distortion had exceed the maximum limitation of the IEEE 519-1992. The highest results were exceeding 57,52 % when inverter does not have any load. After using passive filter that function for reducing the value of harmonic, the total harmonic distortion (THD) current w only 6,837% when inverter does not have any load.